2019
DOI: 10.1002/slct.201902780
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Bioactivity and Mechanical Stability of Mg/Ca Silicate Biocomposites Developed for Tissue Engineering Applications

Abstract: Bioceramics used in hard tissue engineering applications should primarily meet the criteria of mechanical strength and apatite mineralisation of natural bone. In such a scenario, designing of bioceramic composites is inevitable as calcium silicates possess good apatite deposition ability and magnesium silicates show excellent mechanical stability. The present study investigates the influence of calcium (Ca) and magnesium (Mg) ions of the bioceramics on bioactivity and mechanical strength. Binary silicates such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
(90 reference statements)
2
8
0
Order By: Relevance
“…The observed peaks for carbonate group might be due to the breakdown of carbon dioxide in silicate ceramics which causes the asymmetrical stretching vibrations. The vibrational bands obtained for single phasic larnite were in accordance with the previous reports [11,15,20,21,31] …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The observed peaks for carbonate group might be due to the breakdown of carbon dioxide in silicate ceramics which causes the asymmetrical stretching vibrations. The vibrational bands obtained for single phasic larnite were in accordance with the previous reports [11,15,20,21,31] …”
Section: Resultssupporting
confidence: 91%
“…Silicate ceramics builds curiosity as a biomaterial for prosthetic application owing to its ability to induce biomineralization in physiological medium and possess mechanical strength equivalent to bone [9] . Calcium silicates are preferred as a bone graft material due to its good bioactivity and stimulates cell proliferation as well as promotes good osteogenic differentiation when compared to magnesium silicates [10,11] . Among various calcium silicate bioceramics wollastonite has an enormous literature [12–14] and was found to possess bioactive nature higher than the synthetic HAp with better cell response and bactericidal activity [11,15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2. An earlier study reported the steps involved during the phase evolution of wollastonite [22]. A similar mechanism of wollastonite phase formation was observed in the present work.…”
Section: Xrd Investigationsupporting
confidence: 88%
“…The sol-gel combustion method was adopted to synthesise wollastonite as described previously using Ca(NO 3 ) 2 .4H 2 O (98%, SDFCL) and TEOS (98%, Sigma-Aldrich) [22]. Citric acid (99.5%, SDFCL) was used as a fuel and nitrate ions from the metal nitrate performed as an oxidiser.…”
Section: Synthesis and Characterisation Of Wollastonitementioning
confidence: 99%